Specific targeting of proteins to outer envelope membranes of endosymbiotic organelles, chloroplasts, and mitochondria - Lee, Junho; Kim, Dae Heon; Hwang, Inhwan (Frontiers in Plant Science, 2014)
Chloroplasts and mitochondria are endosymbiotic organelles thought to be derived from endosymbiotic bacteria. In present-day eukaryotic cells, these two organelles play pivotal roles in photosynthesis and ATP production. In addition to these major activities, numerous reactions and cellular processes that are crucial for normal cellular functions occur in chloroplasts and mitochondria. To function properly, these organelles constantly communicate with the surrounding cellular compartments. This communication includes the import of proteins, the exchange of metabolites and ions, and interactions with other organelles, all of which heavily depend on membrane proteins localized to the outer envelope membranes. Therefore, correct and efficient targeting of these membrane proteins, which are encoded by the nuclear genome and translated in the cytosol, is critically important for organellar function. In this review, we summarize the current knowledge of the mechanisms of protein targeting to the outer membranes of mitochondria and chloroplasts in two different directions, as well as targeting signals and cytosolic factors.